2014
DOI: 10.1002/2013wr014317
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient dynamics in an oligotrophic arctic stream monitored in situ by wet chemistry methods

Abstract: Diurnal trends in hydrochemical components of stream and river water, especially nutrients, is growing in interest as instrumentation capable of measuring at fine time scales becomes increasingly available. In this growing body of work, there are few studies that simultaneously report the dynamics of the major nutrients nitrate, phosphate, and ammonium through time. We used an in situ nutrient autoanalyzer to simultaneously measure nitrate, phosphate, and ammonium concentrations with wet chemistry methods in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 32 publications
5
18
0
Order By: Relevance
“…However, McNamara et al (2008) reported increases in North Slope Alaska stream NO 3 − in early fall in some, but not all, years, with similar seasonal timing as our reported decrease in soil NO 3 − . Water sampled from the outlet of Toolik Lake continuously into early September in 2006 did not show a similar peak in NO 3 − (Snyder and Bowden 2014), although in 2011, local stream NO 3 − increased in mid-September (W.B. Bowden, personal communication), coinciding with the described decrease in soil NO 3 − in this study.…”
Section: Discussionsupporting
confidence: 53%
“…However, McNamara et al (2008) reported increases in North Slope Alaska stream NO 3 − in early fall in some, but not all, years, with similar seasonal timing as our reported decrease in soil NO 3 − . Water sampled from the outlet of Toolik Lake continuously into early September in 2006 did not show a similar peak in NO 3 − (Snyder and Bowden 2014), although in 2011, local stream NO 3 − increased in mid-September (W.B. Bowden, personal communication), coinciding with the described decrease in soil NO 3 − in this study.…”
Section: Discussionsupporting
confidence: 53%
“…As previously mentioned, the small size of the Imnavait watershed limits the time that waters are subjected to instream photochemical and microbial processing compared to the other study sites. Reduced channelized water transit times likely limit potential instream nitrification of available NH 4 + [ Wollheim et al ., ; Snyder and Bowden , ]. As such, we would expect NO 3 − concentrations to increase and NH 4 + concentrations to decrease further downstream from our Imnavait sampling locating, consistent with the patterns observed at the other larger study sites.…”
Section: Discussionmentioning
confidence: 99%
“…Photooxidation may account for 70-95% of total DOC processed in the water column of lakes and rivers in the region [Cory et al, 2013;Cory et al, 2014]. Similarly, photoammonification of DON [Bushaw et al, 1996;Grzybowski, 2002;Sereda et al, 2012], followed by immobilization or nitrification [Peterson et al, 1997;Wollheim et al, 2001;Snyder and Bowden, 2014], may be an important DON loss mechanism in these systems. Moreover, partial photooxidation stimulates microbial remineralization of otherwise recalcitrant DOC [Cory et al, 2014], and may promote additional DON microbial remineralization postsnowmelt as well.…”
Section: Dissolved Organic Nitrogen Seasonal Dynamicsmentioning
confidence: 99%
“…At the watershed-scale, continuous nitrate monitoring is proving useful for both calculating nutrient loading to downstream waters (Pellerin et al, 2014), as well as understanding the drivers of changes in water quality (Hensley et al, 2014). High frequency measurements are also critical to adequately characterize the variability in surface water nitrate and orthophosphate concentrations at some sites, especially during hydrologic events (Pellerin et al, 2012;Bende-Michl et al, 2013;Ferrant et al, 2013;Carey et al, 2014;Outram et al, 2014;Bowes et al, 2015;Sherson et al, 2015) and during periods when instream biological processing or other factors produce, consume, or alter nutrients prior to downstream export (Pellerin et al, 2009;Heffernan and Cohen, 2010;Cohen et al, 2013;Hensley et al, 2014;Snyder and Bowden, 2014). For example, diurnal nitrate patterns similar to those observed in the Potomac River (Figure 2) have been used to estimate rates and drivers of primary productivity in both freshwater (Heffernan and Cohen, 2010;Cohen et al, 2013) and coastal environments (Johnson et al, 2006;Collins et al, 2013).…”
Section: Advancing Our Understanding Of Watershed Processesmentioning
confidence: 99%